Data from: Brood size matching: a novel perspective on predator dilution - Jaatinen, Kim; Öst, Markus (Dryad, 2021)
A primary benefit of grouping is diluting the individual risk of attack by predators. However, the fact that groups are formed not always by solitary adults but also by subgroups (e.g., families) has been overlooked. The subgroup-specific benefit of predator dilution depends on its relative contribution to total group size. Therefore, the willingness of a subgroup to merge with others should increase the less it contributes to total group size, but the conflicting preferences of partners may result in the preferential merger of similar-sized subgroups. Here, we evaluate how the proportional contribution of subgroups to diluting risk affects group formation. We generate predictions using a bidding game over parental care and test them using data on common eiders (Somateria mollissima), in which females with variable-sized broods may form brood-rearing coalitions. The predictions (1) that size-matched subgroups should have a higher propensity to merge, (2) that predation should increase group formation propensity, and (3) that increased bargaining power, as proxied by female body condition, should increase the time needed to establish partnerships were all supported. Partners do negotiate over their relative contributions to predator dilution, accepting or rejecting partnerships on the basis of this criterion. Our results show that consideration of the size of subgroups before merger is critical in understanding the process of group formation under the threat of predation. EiderField data on eider group formation behaviour.